Energy and economic efficiency of camelina and crambe biomass production on a large-scale farm in north-eastern Poland. (1st May 2018) - Stolarski, Mariusz J.; Krzyżaniak, Michał; Kwiatkowski, Jacek; Tworkowski, Józef; Szczukowski, Stefan
Abstract: The aim of this study was to determine the energy and economic efficiency of Camelina sativa and Crambe abyssinica production on a commercial plantation. The study was based on a three-year large-scale trial. The energy and economic inputs in the production of camelina and crambe were similar and were dominated by the consumption of fertilisers. The average yield of camelina and crambe seeds was very similar but the yield of camelina was more stable. The average energy gain from production of camelina was higher by 4.9% compared with the crambe. The average income from camelina seeds production (876.3 € ha −1 ) was higher by almost 12% than for crambe. The average energy efficiency ratio for production of camelina seeds (2.00) was higher by 5.7% compared with the crambe. The average energy efficiency ratio for the production of total biomass (seeds and straw) of camelina (4.74) was higher by 4.2% compared with the crambe. The revenue from camelina seeds was on average 312 € ha −1 and was 36% higher than that from crambe seeds, while the revenue from camelina total biomass production was on average 432.6 € ha −1 and was 26% higher than the value obtained from crambe production. Highlights: Biomass yield of camelina was more stable compared with crambe. Energy gain from production of camelina was higher compared with crambe. The energy intensity production of camelina was lower compared with crambe. The energy ratio production of camelina was higher by 4.2% compared with crambe. The revenue from camelina seeds production was 36% higher compared with crambe.